2020
DOI: 10.1002/pat.5181
|View full text |Cite
|
Sign up to set email alerts
|

The supplement role of iron oxide and zirconium oxide nanoparticles as an advanced composite compound for enhancing the efficiency of thin‐film nanocomposite membranes

Abstract: In this research, to enhance the efficiency of polyacrylonitrile, iron oxide (Fe3O4) nanoparticles were added to membrane matrix and M(0,1) (PA/FePAN) membrane was fabricated. To boost the effectiveness, the iron oxide/zirconium oxide composite nanoparticles (Zr©Fe) were added to the superficial polyamide layer to synthesize M(1,0) (Zr©FePA/PAN) membrane. In order to investigate the supplement role of Fe3O4 and Zr©Fe nanoparticles, both nanoparticles were added to PAN substrate and PA superficial layer, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
(67 reference statements)
0
4
0
Order By: Relevance
“… 33 A sharp band was obvious at 534.61 cm −1 due to the Fe–O functional group. 27 These peaks consistently appeared within the identical range throughout the spectra of all samples. For the samples that were calcined at 300, 600, and 900 °C, there was a progressive decline in the strength of the band in the 3466 cm −1 range.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“… 33 A sharp band was obvious at 534.61 cm −1 due to the Fe–O functional group. 27 These peaks consistently appeared within the identical range throughout the spectra of all samples. For the samples that were calcined at 300, 600, and 900 °C, there was a progressive decline in the strength of the band in the 3466 cm −1 range.…”
Section: Resultsmentioning
confidence: 71%
“… 26 Peak at 1738.71 cm −1 was attributed to the Zr–OH functional group. 27 A midrange band at 1639.39 cm −1 was noted, possibly originating from the bending of H–O–H coordinated H 2 O molecule. 28 Peak at 1379.79 cm −1 was ascribed to the presence of surface –OH groups in M–OH (either Fe(OH) 2 or Zr(OH) 4 ).…”
Section: Resultsmentioning
confidence: 94%
“…In both TFNC and MTFNC membrane groups, it was observed that with increase in the concentration of nanoparticles up to 0.125 (WV%), the flux passing across the CuS 4 T 3 M 3 and CuS@AA 4 T 3 M 3 increased by 77% and 55% respectively. Increase of both porosity and hydrophilicity is one of the most important factors for the higher membrane flux and less fouling in response to presence of nanoparticles 52 . The rise of concentration of nanoparticles up to 0.1375 (WV%) caused diminished drug flux passing across the CuS@AA 5 T 3 M 3 and CuS 5 T 3 M 3 membranes by 21% and 20% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Increase of both porosity and hydrophilicity is one of the most important factors for the higher membrane flux and less fouling in response to presence of nanoparticles. 52 The rise of concentration of nanoparticles up to 0.1375 (WV%) caused diminished drug flux passing across the CuS@AA 5 T 3 M 3 and CuS 5 T 3 M 3 membranes by 21% and 20% respectively. The reduction of membrane flux at higher nanoparticle concentrations can be due to diminished membrane porosity (Figure 12).…”
Section: Filtration Behavior Of Tfc Tfnc and Mtfnc Membranesmentioning
confidence: 97%